NATIONAL TECHNOLOGICAL INITIATIVE AS THE STRATEGIC DIRECTION OF THE TECHNOLOGICAL DEVELOPMENT OF RUSSIA - E. V. Sibirskaya; L. V. Oveshnikova (Статистика и экономика, 2018)
Russia, having lost a significant part of a high-tech industrial complex during the reforms (1993–2000), sharply reducing the state support of scientific research and development, has turned into a power dependent on the conjuncture in the hydrocarbon energy market and from foreign sup-plies of technologies, consumption goods, including those necessary for life support, thus being on the "technological needle". The main factor of development was the resource-producing complex. This situation had a negative impact on the pace of the country's development, on its defense capability and created real prerequisites for the loss of technological, economic, and, in the long run, political sovereignty and disintegration of the state. Nevertheless, the availability of natural resources along with human capi-tal and geographic location is a global competitive advantage of theRussian Federation, and the task is to use this advantage maximally as one of the first echelon countries in the emerging world order. One of the most important tasks was the search for such a direction of technological devel-opment that allows, on the one hand, to preserve Russia's position in the world market of traditional products; on the other – to strengthen positions in the markets of products with a higher degree of processing of Russian raw materials (oil and gas complex and agro-industrial complex); and finally – to master new "growth points" (services, new markets, talents, technologies) in the world market of high-tech products and services. The set tasks assume several solutions. First, scientific and technological development should be based on the strategy of scientific and technological development of theRussian Federationand the national technological initiative, as it sets both resource constraints and priorities in the needs of the economy in new products and new technological solutions. Secondly,Russiashould take into account existing and emerging trends in the development of science and technology directions and priorities of scientific and tech-nological policy of the leading countries. To ensure access to a new technological level of economic development, domestic advanced development and scientific solutions are needed. It is necessary to emphasize the directions in which the powerful technological potential of the future accumulates. In this regard, at present, state support for high-tech and technologyintensive business is rel-evant inRussia. The long-term comprehensive program "National Technological Initiative" is of great importance to create the necessary conditions for ensuring the leadership of Russian organiza-tions in new high-tech markets that will shape the structure of the world economy in the next 15–20 years. In "National Technological Initiative", the state defined "points of growth" in the develop-ment of the economy, i.e. key areas that have a pre-material realization in the branches of high-tech business (EnergyNet, FoodNet, HealthNet, AeroNet, AutoNet, FinNet, NeuroNet, TechNet). The formation of scientific and technological reserve in these key areas will create globally competitive high-tech products and services in the interests of social and economic development ofRussia.